New indolizine–chalcones as potent inhibitors of human farnesyltransferase: Design, synthesis and biological evaluation. Issue 15 (1st August 2016) - Moise, Iuliana-Monica; Ghinet, Alina; Belei, Dalila; Dubois, Joëlle; Farce, Amaury; Bîcu, Elena
Graphical abstract: Abstract: A new family of indolizine–chalcones was designed, synthesized and screened for the inhibitory potential on human farnesyltransferase in vitro to identify potent antitumor agents. The most active compound was phenothiazine2a, exhibiting an IC50 value in the low nanomolar range, similar to that of known FTI-276, highly potent farnesyltransferase inhibitor. The newly synthesized indolizine–chalcones2a –d constitute the most efficient inhibitors of farnesyltransferase bearing a phenothiazine unit known to date.